Lateral thyroid cartilage thyrotomy approach to an embedded paraglottic fishbone - Wong, Hui Tong; Tham, S.Y.; Elangkumaran, Krishnan; Ng, W.S.J.; Sia, Kian Joo (Royal College of Surgeons of England, 2017)
Fishbones are of particular interest to otolaryngologists. Most fishbones can be removed transorally or via endoscopic guidance. Transcervical neck exploration is occasionally necessary, especially in cases of an embedded foreign body. Computed tomography is the most sensitive and specific imaging modality for identifying embedded fishbones. To our knowledge, this is the first reported case of a laryngeal foreign body embedded in the paraglottic space that was removed using an open approach via a lateral thyroid cartilage window.